JAMINAN FIDUSIA DI INDONESIA (TATA CARA PENDAFTARAN DAN EKSEKUSI) - Abdullah, Junaidi (BISNIS, 2016)
Debtor when asking to financing financing institution(creditors) usually use the guarantee in the form of objects thatmove and things that do not move. When guaranteed in theform of moving objects, then creditors will bind him withfiducia warrant.. Fiducia warrant is the right guarantees formoving objects either exist or not exist and objects do not moveespecially the building could not be burdened by the yoke rightsreferred to in Law Number 4 of 1996 on the Rights of the yokethat remain in the mastery of a Warner fiducia warrant, ascollateral for certain debt repayment, which provide thepreferred position to the recipient fiducia warrant against othercreditors. (Article 1 of Act No. 42 The year 1999 about fiduciawarrant). Fiducia warrant must be made by deed autentik andmust be registered in the registration office fiducia warrant andwant to warranty certificate fiducia warrant. But sometimes thedebtor does not perform its obligations to the debtor, so that thedebtor has the right to execute the things that have beenpledged fiducia warrant. But sometimes the implementation ofthe execution get resistance from the debtor, because thecreditors with using services debt collector take force objectsfiducia warrant without doing the negotiations even tear in thestreets. For that the police can provide security servicesexecution of parties willing to execute the object fiduciawarrant.